KONDISI EKONOMI MASYARAKAT SEBELUM DAN SESUDAH BERDIRINYA PT. BINA PRATAMA SAKATO JAYA SOLOK SELATAN 1 (BPSJ-SS1) DI KANAGARIAN ABAI KECAMATAN SANGIR BATANG HARI KABUPATEN SOLOK SELATAN - Afrina Suriati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
This study aims to get the data, analyze and discuss the process neighbor economic conditions before and after the establishment of PT. Bina Jaya Pratama Sakato South Solok 1 (BPSJ-SS1) in Kanagarian Abai Sangir Batang Hari District of South Solok. This study discusses the conditions of livelihood, income conditions and the condition of public welfare in Kanagarian Abai Sangir Batang Hari District of South Solok before and after the establishment of PT.BPSJ-SS1. This type of research is descriptive research is a form of research that aims to describe or depict things as they are and reveal the factors that exist. The population in this study is were all the people who work in PT.BPSJ SS-1 amounted to 1025, the sample of respondents in this study were drawn in a proportional random sampling of 100% of the total population is 102 people. The results of the study include: (1) Prior to the establishment of PT.BPSJ SS-1 condition subsistence farming (57.8%), after the establishment of PT.BPSJ SS-1 to bring positive change to the condition of people's livelihood is now living as a factory worker in PT.BPSJ SS-1, (2) Prior to the establishment of PT.BPSJ SS-1 of its income under <IDR. Perbulanya 1,000,000 (80.4%), after the establishment of PT.BPSJ SS-1 to bring positive changes to the conditions of income between Rp. 1000000-2000000 perbulanya (74.5%).